Cancer Stem Cells and Molecular Biology Test in Colorectal Cancer: Therapeutic Implications - Rustam Effendi-YS (Interna Publishing, 2018)
Colorectal cancer (CRC) is the third most frequent cancer in males, the second in females, and is the second leading cause of cancer related death worldwide. Within Indonesia's 250 million population, the incidence rates for CRC per 100,000 population were 15.2 for males and 10.2 for females, and estimated 63,500 cases per year.  More than 50% of colorectal cancer patients will develop metastasis. CRC is still the main cause of tumor-related death, and although most CRC patients are treated with surgery to remove the tumor tissue, some of the CRC patients recurred. Chemotherapy used as adjuvant or neoadjuvant therapy also has several problems, in which these treatments are useless in tumor cells with chemo-resistance. Molecular testing of CRC from tumor tissues has important implications for the selection of treatment. Biomarkers can be used as prognostic value, molecular predictive factors, and targeted therapy. Recent research reported that, cancer stem cells (CSCs) are considered as the origin of tumorigenesis, development, metastasis and recurrence. At present, it has been shown that CSCs existed in many tumors including CRC. This review aims to summarize the issue on CSCs, and the future development of drugs that target colorectal cancer stem cells.